National Language Planning and Language Shifts in Malaysian Minority Communities: Speaking in Many Tongues - Dipika Mukherjee, Maya Khemlani David (Amsterdam University Press, 2011)
Most research focuses on government-determined language policies. However, it is important to evaluate language choices and language use by the common man, too, as inconsistency between the two can lead to unrest. Language planning and policy has never been an easy task for those involved in it. Whatever planning or policy is specifically utilised in choosing the national language or official language, the consequences are crucial because they affect not only a few individuals but the entire nation. The selection process is a crucial imperative, for it involves social and political factors. It must be noted that whatever language is chosen or selected, it must serve a variety of functions: it must be a language that is unifying, separatist, prestigious and has frame-ofreference function (Holmes 2001). Language planning and policymaking is also complicated, for it includes the regular patterns of choice, beliefs about choices, values regarding varieties or variants of particular languages, and also the efforts made in order to change the choices and beliefs of others (Spolsky 2004). When studying speech communities and their actual language practices, one often finds inconsistencies between nationally planned language policies and language use. Therefore it is vital for policymakers to be in touch with the linguist; the linguist should in any case be actively involved when choosing the national or official language of a country.Language Planning and Language Policy (LPLP) is a problem in many multilingual and multicultural developing countries. With the people’s diversity in language and culture, national unity has been a commonly sought objective. It has been a known fact that in some countries, national unity leading to economic development can be the result of language policy. However, there have also been a number of problems about building national identity and national unity as a result of choosing a particular language as the national language.